1998
DOI: 10.1002/chin.199836173
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and Antiinflammatory Activity of Some 3‐(2‐Thiazolyl)‐1,2‐benzisothiazoles.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Furthermore, 1,3,4-thiadiazoles were recently reported as highly anti-inflammatory [ 10 , 11 ], and anticonvulsant agents [ 10 , 12 ]. Also, thiazoles and their derivatives found application in drug development for the treatment of allergies [ 13 ], hypertension [ 14 ], inflammation [ 15 ], schizophrenia [ 16 ], bacterial [ 17 ] and HIV infections [ 18 ]. Encouraged by all these findings and in continuation of our ongoing research program investigating the utilization of compound 1 as versatile and useful building blocks for the synthesis of a wide variety of bis-heterocycles systems [ 19 , 20 ], we report in the present work an efficient and rapid method for the synthesis of a series of thienothiophene pendant to thiadiazole or thiazole moieties.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 1,3,4-thiadiazoles were recently reported as highly anti-inflammatory [ 10 , 11 ], and anticonvulsant agents [ 10 , 12 ]. Also, thiazoles and their derivatives found application in drug development for the treatment of allergies [ 13 ], hypertension [ 14 ], inflammation [ 15 ], schizophrenia [ 16 ], bacterial [ 17 ] and HIV infections [ 18 ]. Encouraged by all these findings and in continuation of our ongoing research program investigating the utilization of compound 1 as versatile and useful building blocks for the synthesis of a wide variety of bis-heterocycles systems [ 19 , 20 ], we report in the present work an efficient and rapid method for the synthesis of a series of thienothiophene pendant to thiadiazole or thiazole moieties.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds having a furfyl group as substitutent (4, 9, 14) revealed the least % inhibition of oedema in rat paw, while compounds having phenyl ring with methoxy group either at ortho or para-position (as substituent) exhibited the maximum activity. Furthermore, compounds having a phenyl group as substituent (3,8,13) and Hence, it can be concluded that 1. Azetidinones possess more potent activity than their corresponding arylidenes.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was reported that liver cancer is one from the top ten human cancers worldwide and among the top five of cancers in terms of mortality [ 2 , 3 ]. A literature survey revealed that thiazole derivatives had many biological activities as antihypertension [ 4 ], antifungal [ 5 ], antimicrobial [ 6 , 7 ], anti-inflammatory [ 8 ], antioxidant [ 9 ], antitubercular [ 10 ], and anticancer [ 11 14 ]. Moreover, 1,3,4-thiadiazole derivatives had many biological activities such as antibacterial, antifungal, antituberculosis, anti-hepatitis B viral, antileishmanial, anti-inflammatory, analgesic, CNS depressant, antioxidant, antidiabetic, molluscicidal, antihypertensive, diuretic, analgesic, antimicrobial, antitubercular, anticonvulsant and anticancer [ 15 – 24 ].…”
Section: Introductionmentioning
confidence: 99%